Desoria calderonis sp. nov., a new species of alpine cryophilic springtail (Collembola: Isotomidae) from the Apennines (Italy), with phylogenetic and ecological considerations - Valle, Barbara; Cucini, Claudio; Nardi, Francesco; Caccianiga, Marco; Gobbi, Mauro; Di Musciano, Michele; Carapelli, Antonio; Ficetola, Gentile Francesco; Guerrieri, Alessia; Fanciulli, Pietro Paolo (European Journal of Taxonomy, 2021)
We describe and delimit with integrative taxonomy the new springtail species Desoria calderonis sp. nov. (Collembola: Isotomidae). This cryophilic species is strictly linked to the supraglacial stony debris of the isolated Calderone glacier (Central Apennines, Italy), one of the southernmost glaciers of Europe. Desoria calderonis sp. nov. could belong to the nivalis-complex, a group of European mountain species included in the violacea-group. Genetic analysis (COI mtDNA barcoding) confirms the morphological attribution to the genus Desoria Nicolet in Desor, 1841, but highlights that the genus, in its current definition, is polyphyletic. We specify the peculiar micro-habitat preferences and highlight the threat of extinction for this cryophilic species in the context of the ongoing climate change and subsequent risk of complete disappearance of the glacier.